Presence of the CYP2B6 516G>T polymorphism and increased plasma Efavirenz concentrations in South African HIV infected patients - Gounden, Verena (My University, 2011)
Introduction The 516G>T polymorphism in exon 4 of the CYP2B6 gene has been linked to increased plasma Efavirenz (EFV) levels. EFV levels can predict therapeutic efficacy and are related to the likelihood of developing adverse central nervous system (CNS) effects. The aims of this study were to a) determine the presence of the 516G>T and other possible CYP2B6 exon 4 polymorphisms in a South African group of HIV-infected individuals and b) to investigate the relationship between the EFV plasma concentrations, the CYP2B6 516G>T polymorphism and the occurrence of CNS related side effects in this group of patients. Methods Data from 80 patients are presented. Genetic polymorphisms in exon 4 of the CYP2B6 gene were identified using PCR amplification of this region followed by sequencing of the amplification products. EFV levels were analysed by Ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). Assessment of the presence of CNS related side effects following EFV initiation were elicited with the use of a questionnaire together with physical examination. Results Plasma EFV concentrations displayed high inter-individual variability amongst subjects with levels ranging from 94 μg /l to 23227 μg/l. 23 % of patients were TT homozygous for the 516G>T polymorphism. These patients had significantly higher EFV levels vs. those with the wild (GG) genotype (p <0.05). Those who experienced no side effects had significantly lower EFV plasma concentrations vs. the group which experienced the most severe side effects (p< 0.05). iv Conclusion The significant association between the 516G>T polymorphism and plasma EFV concentrations has been demonstrated in a South African cohort. A rapid and sensitive method for the measurement of plasma EFV was developed and validated.
MMed, Chemical Pathology, Faculty of Health Sciences, University of the Witwatersrand
Keywords: HIV; polymorphism; plasma Efavirenz concentrations